Neural, renal and retinal hamartomas with cutis vertis gyrata a rare presentation in tuberous sclerosis complex - Shanbhag, Nita U.; Bhatt, Nupur Vijay; Patil, Sharmila; Cholera, Priyadarshini (International Journal of Research in Medical Sciences, 2017)
Tuberous sclerosis complex characterised by multiple benign tumours, is caused by mutation in the genes TSC1 and TSC2 coding for Hamartin and Tuberin respectively. We report a case of a 17 year old female patient who presented with classical Vogt’s triad characterized by seizures, mental retardation and adenoma sebaceous. She presented with Cutis Vertis Gyrata in addition to multiple retinal astrocytic hamartomas in her right eye with retinal pigment epithelium changes in both eyes and a normal anterior segment examination. Magnetic resonance imaging (MRI) of the brain showed subependymal giant cell astrocytomas and cortical tubers. Ultrasound of the abdomen showed bilateral renal angiomyoliposis. We are presenting this case as retinal hamartomas with five Major criteria are seen along with secondary Cutis Vertis Gyrata which is an extremely rare presentation of Tuberous sclerosis. Absence of most of the Minor criteria is not to be excluded.